Implantation of three-piece silicone toric additive IOLs in challenging clinical cases with high astigmatism - Thomas, Bettina C.; Auffarth, Gerd U.; Reiter, Josef; Holzer, Mike P.; Rabsilber, Tanja Marina (Journal of refractive surgery, 2013)
Purpose: To analyze the refractive outcomes and safety of three-piece silicone toric sulcus-fixated add-on intraocular lenses (IOLs) (HumanOptics/Dr.Schmidt Intraocularlinsen, Erlangen, Germany) in complex clinical cases with high astigmatism such as in cases with previous penetrating keratoplasty. - Methods: Interventional case series of 21 eyes of 20 patients enrolled at two German centers. Functional results including power vector analysis, accuracy of IOL power calculation, rotational stability, and postoperative complications were evaluated from 2 months to 6 years postoperatively. - Results: The preoperative subjective cylinder exceeded or was equal to −6.00 diopters (D) in 81% of eyes (range: −2.00 to −17.00 D). The median follow-up period was 7.6 months (range: 57 days to 6 years). The efficacy analysis focused on the 2 to 6 months follow-up visit. Postoperatively, there was a median reduction of astigmatism by 70.59% (subjective cylinder range: 0.00 to −5.00 D), improvement of uncorrected distance visual acuity, and unchanged median corrected distance visual acuity. The attempted spherical equivalent was achieved within ± 0.50 D in 45% and within ± 1.00 D in 65% of cases. Five eyes received secondary surgical alignment of axis. Other complications related to the surgical procedure were mainly transient shortly after implantation, such as intraocular pressure elevation (2 of 21 eyes) or corneal edema (2 of 21 eyes). Persisting changes were seen only in rare cases and included pigment dispersion (1 of 21 eyes) or corneal edema requiring a second keratoplasty within 9 months after surgery (2 of 21 eyes). - Conclusions: Toric add-on IOLs may be useful in reducing high astigmatism and anisometropia and increasing spectacle independence even in complex clinical conditions with high refractive errors.